Developing Framework for Teaching Technical Skills to Metalwork Undergraduates in Vocational-Based Education in Nigeria - Venatius, Arikpo Sampson; Aede Hatib , Musta’amal; Ekwok, Ogumbe Boniface (Journal of Technical Education and Training, 2023)
The rising prevalence of unemployment and high demands at workplaces require vocational-based education teachers to devise an appropriate practical skills procedure. Teaching through a well-designed instructional procedure that stresses learners' involvement in skill practice is an alternative to cultivating skills. This study proposes a scientific procedure for implementing a vocational-based education curriculum in colleges of education by identifying key activities that lecturers and industrial technicians considered to be important for teaching undergraduate technical skills in Nigeria. There is no accepted framework for teachers to teach skills and evaluate their instruction. Efforts have been made to create such a prospective framework, but none has been put into use (Bannister et al. 2018) because they are poorly understood (Sarker, Vincent, and Darzi 2005). The study utilized the Delphi research strategy to gain consensus about the processes and activities involved in teaching skills. Then, employed the Four D Model (4-D model), which included the steps of Task identification, Material arrangement, Task execution, and Task evaluation, was developed in the research. We test a model of factors predicting the appropriate teaching model. Structural Equation Modeling (SEM) was used to analyze the data. The result revealed the differential effect of the variables considered.  However, the activities in each stage were utilized to design the scientific procedure for teaching technical skills in colleges of education. Because learning skills that are shielded in hands-on activities rely upon teaching procedures and skill practice opportunities, we concluded that effectively utilizing this scientific framework in colleges would improve students’ practical skills acquisition and make them active in the learning process.